Muslims' Challenges in the Era of Modernisation (The LGBT+ Phenomenon in Indonesia and the Strategy of Persuasive Da'wah Approach) - Fauziah Ramdani (Fakultas Dakwah dan Ilmu Komunikasi, 2024)
LGBT+ is a global phenomenon that challenges Muslims and da'wah actors in particular. This study aims to describe the phenomenon of LGBT+, especially in Indonesia, and explore several strategies of da'wah approaches that can be done both as a preventive measure and when LGBT+ deviations occur. The research method used is qualitative with library research using twenty-one scientific journal references to examine and find explanations related to LGBT+. The results showed (1) LGBT+ is a social deviation that is globally increasingly rapid development and even constitutionally in some countries recognized as an abnormal relationship as recognition of human rights that get special treatment. (2) Indonesia as one of the countries with data as many as 26 million Facebook users openly identify themselves as LGBT with the number of gays in Indonesia has reached 20,000 people and even more. (3) From an Islamic perspective, the LGBT+ movement and struggle is considered a struggle that violates biological and theological foundations and principles. Qur'anic verses explain the prohibition of LGBT+ behavior, q.s.Annisa:119, Al-A'raf: 80-81 and surah Hud: 78.(4) Islam pays close attention to this phenomenon by implementing several distinctive da'wah approaches that can be carried out by da'i or da'wah groups. As a preventive measure, for example, by mainstreaming to children as early as possible about faith education, morals and morals, physical and sex education gradually. (5) A da'wah approach that touches cognitive, affective and behavioral aspects by always considering the principles of da'i ability, sociological, psychological principles as well as the principles of effectiveness and efficiency of da'wah. Two major strategies carried out are senitmentil and rational strategies. Touching the heart of the object of da'wah with reflective messages while presenting logical messages wrapped in scientific research built on the foundation of sharia to show and open the hearts and minds of LGBT+ people about the dangers of these bad actions.